G4 DNA: at risk in the genome - Davis, Luther (Nature Publishing Group, 2011)
A study in this issue offers new evidence for G-quadruplex (G4) DNA structure formation in vivo and its contribution to genomic instability, and identifies specific cellular mechanisms to cope with such threats.